Changes in the Spatial Structure of Industry in the Małopolska Region - Ciechowski, Marek (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2014)
The main goal of the paper is to analyze changes in the spatial structure of industry in the Małopolska region. In particular, the research focuses on industrial change in the period of European integration and during economic crisis. On the basis of the analysis, it was showed that the spatial structure of industry is characterized by stability and has not changed in recent years. However, industrial dispersal and industrial development in the outer zone of the Cracow Metropolitan Area was observed. The Cracow Metropolitan Area, western parts of the region, and a few cities, e.g. Tarnów, Nowy Sącz and Gorlice, are still the most industrialised areas of the Małopolska region.